2017
DOI: 10.1002/hep.29297
|View full text |Cite
|
Sign up to set email alerts
|

Palliative care access for hospitalized patients with end‐stage liver disease across the United States

Abstract: From 2006 to 2012 the use of PC in ESLD patients increased substantially; socioeconomic, geographical, and ethnic barriers to accessing PC were observed. (Hepatology 2017;66:1585-1591).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
53
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(65 citation statements)
references
References 33 publications
(65 reference statements)
7
53
2
Order By: Relevance
“…Teaching hospitals are likely to have an established integrated palliative care system and higher availability of specialist palliative care services 49. Further studies are needed to achieve equity of access to specialist palliative care and adequate care transfer between different clinical settings for people with ILD.…”
Section: Resultsmentioning
confidence: 99%
“…Teaching hospitals are likely to have an established integrated palliative care system and higher availability of specialist palliative care services 49. Further studies are needed to achieve equity of access to specialist palliative care and adequate care transfer between different clinical settings for people with ILD.…”
Section: Resultsmentioning
confidence: 99%
“…Other retrospective studies showed that only 1 in 3 terminally hospitalized patients received PC consultation, with lower rates among LT candidates and racial or ethnic minorities . Overall, only 5% of all hospitalized patients with multiple cirrhosis decompensations had documented PC consultations, and these patients rarely received a PC referral outside of the hospital, with nearly 90% of 1 transplant center’s PC referrals occurring during a hospital admission …”
Section: The Benefits Of Pc In Esldmentioning
confidence: 99%
“…These shortcomings may be exaggerated among LT candidates with early goals‐of‐care discussions for these patients occurring at half the rate of LT noncandidates (20% versus 40%) . Those receiving care at larger hospitals or with an existing do‐not‐resuscitate order or a diagnosis of cancer (HCC or metastatic disease) are more likely to receive PC …”
Section: The Benefits Of Pc In Esldmentioning
confidence: 99%
“…Over the past decade, however, referral of patients with ESLD to PC services has slowly increased, with a recent publication documenting a rise in referral rate from 1% in 2006 to 7% in 2012 . Despite this, several inequalities in access to PC services remain.…”
Section: The Role Of Palliative Carementioning
confidence: 99%
“…Despite this, several inequalities in access to PC services remain. Patients with ESLD and low socioeconomic status, Hispanic ethnicity, those who reside in the northeastern part of the United States, and those treated in small and nonteaching hospitals were less likely to receive a PC review . Conversely, patients with HCC or a metastatic cancer were more likely to receive a PC review, likely related to the greater awareness of the benefits of PC for patients with cancer …”
Section: The Role Of Palliative Carementioning
confidence: 99%